The political economy of South Africa's transition policy perspectives in the late 1990s - Michie, Jonathan; Padayachee, Vishnu (Dryden Press, 1997)
This edition analyzes and discusses economic policies over a range of macroeconomic and industrial areas which are required to see through the reconstruction and development of the South African economy. It explores the recent history and politics of the processes of economic policy formulation.